THE INFLUENCE OF REGIONAL PECULIARITIES ON HOTEL FACILITIES IN KASHKADARYA - Berdiyev Jasur Koldoshevich (Ecominds Press, 2025)
The article analyzes key regional features, including geographic location, climate conditions, cultural heritage and economic factors. The ways of adaptation of hotels to local conditions are considered, including architectural solutions, service innovations and marketing strategies. The main attention is paid to how hotel businesses can use these features to increase their competitiveness and improve efficiency indicators.
Keywords: Hotel business, Kashkadarya region, efficiency of hotel industry, tourism, architectural solutions, service innovations, marketing strategies, sustainable development, business tourism, regional factors.